Studi Literatur : Perkembangan Teknologi Firewall Dan Strategi Pertahanan Jaringan Pada Sistem Komputer - Cut Tarina; Nazwa Ismara; Lili Mahara; Alysa Alysa; Nahwah Azimah (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
The rapid advancement of information technology has significantly increased dependence on digital networks, making network security a critical concern amid the growing complexity of cyber threats. Traditional security mechanisms are no longer sufficient to address modern attacks such as malware, Distributed Denial of Service (DDoS), ransomware, and application-based intrusions(Bellamkonda, 2024; Patel, 2024). This study aims to systematically examine the development of firewall technologies from early generations to modern solutions and to analyze network defense strategies applied to mitigate contemporary cyber threats. This research employs a literature review method by analyzing scientific journals, textbooks, and international standards related to network security, firewall technologies, and defense strategies published between 2020 and 2025. The collected literature was analyzed using qualitative descriptive analysis to identify trends, characteristics, and challenges in firewall implementation. The results indicate that modern firewalls, particularly Next-Generation Firewalls (NGFW) and cloud-based firewalls, offer enhanced capabilities such as deep packet inspection, application control, and real-time threat prevention(George & George, 2021; Patel, 2024). However, their effectiveness largely depends on proper configuration and integration with layered security strategies, including defense in depth, Zero Trust Architecture, IDS/IPS, VPN, and SIEM(Bellamkonda, 2024; Rose et al., n.d.). Despite their advantages, challenges such as high implementation costs, system complexity, and performance impact remain significant considerations.